Clinical course of thyroid function and thyroid associated-ophthalmopathy in patients with euthyroid Graves’ disease - Suzuki N (Dove Medical Press, 2018)
Nami Suzuki,1 Jaeduk Yoshimura Noh,1 Toshiaki Kameda,1 Ai Yoshihara,1 Hidemi Ohye,1 Miho Suzuki,1 Masako Matsumoto,1 Yo Kunii,1 Kenji Iwaku,1 Natsuko Watanabe,1 Koji Mukasa,1 Ai Kozaki,2 Toshu Inoue,2 Kiminori Sugino,1 Koichi Ito1 1Department of Internal Medicine, Ito Hospital, Tokyo, Japan; 2Department of Ophthalmology, Olympia Eye Hospital, Tokyo, Japan Background: Euthyroid Graves’ disease (EGD) is a rare condition defined as the presence of thyroid-associated ophthalmopathy (TAO) in patients with normal thyroid function. Due to the rarity of this disease, only a limited number of studies and case reports are available for further evaluation of the characteristics of the disease. The aim of this study was to examine the changes in the thyroid function, thyrotropin receptor antibodies (TRAb) and eye symptoms, and then determine whether TRAb is related to TAO in EGD patients. TRAb in this study was defined as including both thyrotropin-binding inhibitory immunoglobulin (TBII) and thyroid-stimulating immunoglobulin (TSAb). Patients and methods: Medical records of patients diagnosed with EGD were reviewed. Ophthalmologists specializing in TAO examined the eyes of all subjects. Results: Of the 58 patients diagnosed with EGD, 24.1% developed hyperthyroidism, while 3.4% developed hypothyroidism. A total of 72.4% of the 58 patients remained euthyroid throughout the entire follow-up period. At the initial presentation, TBII and TSAb were positive in 74.5% and 70.5%, respectively. Ophthalmic treatments were administered to 30 (51.7%) out of the 58 patients. A significant spontaneous improvement of the eye symptoms was found in 28 of the EGD patients who did not require eye treatments. EGD patients exhibited positive rates for both TBII and TSAb, with the number of the TRAb-positive patients gradually decreasing while the eye symptoms spontaneously improved over time. There were no correlations found between TRAb at initial presentation and the eye symptoms. Conclusion: TBII and TSAb were positive in about 70% of EGD patients at their initial visit. Thyroid functions of EGD patients who have been euthyroid for more than 6.7 years may continue to remain euthyroid in the future. Keywords: euthyroid Graves’ orbitopathy, euthyroid Graves’ ophthalmopathy, thyroid-associated ophthalmopathy, TSH receptor antibody, thyroid-stimulating immunoglobulin